The Prevalence and Experience of Harassment of People with Mental Health Problems Living in the Community in Iran - Sara Mahdavian; Somayeh Yousefi; Mohammad Reza Mohammadi; Ali-Akbar Nejatisafa; Mohammad Arbabi; Sharzad Izadi; Kathryn M. Berzins (Iranian Journal of Psychiatry, 2007)
Objective: There have been concerns about people with mental health problems experiencing harassment in the Iranian community. This study measures the prevalence and nature of harassment experienced by individuals with mental health problems and compares them with the general population. Methods : Face to face interviews were conducted by trained interviewers to ascertain experiences of harassment. Interviews were carried out with 112 individuals with mental health problems and with 104 individuals from the general population. Results: Sixty-one per cent of people with mental health problems reported experiencing harassment, nearly ten times more frequently than those in the general population (7%). Among the people with mental health problems, being female, having higher levels of education, or being unemployed were significantly associated with experiencing harassment. The harassment commonly involved verbal abuse, often made reference to individuals' mental health problems and was primarily committed by family members . Conclusions: A significantly higher prevalence of harassment was reported among individuals with mental health problems living in the community than in the general population sample. Mental health professionals should proactively ask their service users about their experiences at home, and educational interventions are recommended, particularly for families of those with mental health problems.